Pemberian Kelonggaran Waktu Pemeriksaan Penundaan Kewajiban Pembayaran Utang Di Pengadilan Niaga - Dianda Dyassaputri; Nyulistiowati Suryanti; Aam Suryamah (Legal Spirit, 2023)
Article 2 letter C SEMA 1 of 2020 stipulates that the time limit for PKPU may exceed the time limit due to forced circumstances, which are not in line with the time provisions in the UUKPKPU. This study aims to examine and see the position of SEMA 1 of 2020 in the hierarchy of laws and regulations and the legal consequences of the enactment of SEMA 1 of 2020. The research method used is the normative juridical method with research specifications that are descriptive analytical, that is to describe laws and regulations analytically applicable regulations and legal theories are related to the issue of provisions for the time of postponement of debt payment obligations. The results of the study concluded that the position of SEMA 1 of 2020 is not included in the hierarchical arrangement of laws and regulations as stipulated in Article 7 paragraph 1 of Law Number 12 of 2011 or its position is under UUKPKPU which is recognized as long as it fulfills the requirements as stipulated in Article 8 of Law Number 12 of 2011 2011 and the legal consequence of the enactment of SEMA 1 of 2020 is that there is no legal certainty in paying debts to creditors because the settlement of debts and receivables through PKPU institutions will take a longer time than the provisions in UUKPKPU.